Pengaruh Transfer Pricing, Koneksi Politik dan Likuiditas Terhadap Agresivitas Pajak (Survey Terhadap Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2016-2019) - Anita Nur Fadillah; Ita Salsalina Lingga (Universitas Kristen Maranatha, 2021)
Abstract Tax aggressiveness is a tax avoidance that is carried out excessively by a business entity which leads to tax evasion. This will have an impact on reducing state revenue from taxes. There are many factors that trigger aggressive tax avoidance. This research is intended to examine the effect of transfer pricing, political connection and liquidity on tax aggressiveness both partially and simultaneously. The population in this study are mining industry entities listed in the Indonesian Stock Exchange for the year of 2016-2019. The sample selection is determined by purposive sampling method. Samples obtained as many as 8 companies for 4 years with a total of 32 samples. Analysis of data uses multiple regression. The result findings indicate that in partially there is no influence of transfer pricing and liquidity on tax aggressiveness, while political connection affects tax aggressiveness. Furthermore, in simultaneously transfer pricing, political connection and liquidity affect tax aggressiveness. Keywords : Transfer Pricing, Political Connection, Liquidity, and Tax Aggressiveness